Influenza Virus Genomic Mutations, Host Barrier and Cross-species Transmission - Xiong, Wenyan; Zhang, Zongde (Current Genomics, 2025)
Influenza is a global epidemic infectious disease that causes a significant number of illnesses and deaths annually. Influenza exhibits high variability and infectivity, constantly jumping from birds to mammals. Genomic mutations of the influenza virus are a central mechanism leading to viral variation and antigenic evolution. Amino acid substitutions and avoidance of microRNA recognition elements are crucial in facilitating the virus to cross species barriers. This review summarizes the types of genomic mutations in the influenza virus, their roles and mechanisms in crossing species barriers, and analyzes the impact of these mutations on human health.
Keywords: microRNA recognition elements